Utilization Of Household Organic Waste Into Eco-Enzyme For Sustainable Waste Management - Nadya Ambarwati; Fajar Jamaluddin Sandhori, S.Farm., M.Farm.; Reviany Vibrianita Nidom; Rismawati; hanif Rifqi Prasetyawan; intan ayu kusumapramushinta; asri wido mukti; asti Rahayu; ira Purbosari; novamei Indriani; fikria marfuatin nur; annisa Rosita Hafiizh (JURNAL PENGABDIAN TEKNOLOGI TEPAT GUNA, 2026)
This community service program aimed to improve community knowledge and skills in managing household organic waste through the production of eco-enzyme. The activity was conducted in RT 4, Wage Village, Taman District, Sidoarjo Regency, using counseling, hands-on training, and questionnaire-based evaluation methods. A total of 30 participants attended the training, with 16 participants involved in the evaluation. The results showed that participants understood the material well, were interested in producing eco-enzyme independently, and recognized its benefits for waste management and household use. The program successfully increased community awareness of environmentally friendly organic waste management and demonstrated the potential economic value of eco-enzyme products. Therefore, eco-enzyme production can serve as a simple and sustainable alternative for reducing household organic waste.